Electromagnetic field features at interaction of relativistic electron with matter - Naumenko G. A. Gennadiy Andreevich; Sukhikh L. G. Leonid Grigorievich; Popov Yu. A. Yuriy Anatolevich; Shevelev M. V. Mihail Viktorovich (2011, 2011)
Title screen